Design, construction and evaluation of a dual device with cellular / satellite coverage for mobile asset tracking technology transfer through - Arévalo López, Johnny Alexander; Ortiz Niño, Marco Andrés; Ferro Escobar, Roberto; Paz Penagos, Hernán (Universidad Santo Tomás, 2015)
This paper presents the design, construction and evaluation of the wireless device OSP cellular and satellite coverage for localization and tracking of mobile assets in Colombia (public transport, freight, carriers, etc.). The development of this product integrates hardware, software and communications interfaces, and it is aligned with a need identified in the market by the company One Solution Position: OSP LTD. With this technology transfer is to improve in offering wireless services for mobile asset tracking using a dual cellular/satellite, versatile, economical, low-power, limited only international standards FCC and CE Mark.

Este artículo presenta el diseño, construcción y evaluación de un dispositivo inalámbrico de cobertura celular y satelital para la localización y el rastreo de activos móviles en Colombia (transporte público, transporte de carga). El desarrollo de este producto integra hardware, interfaces de comunicaciones y software, y está alineado con una necesidad detectada en el mercado por la empresa One Solution Position: OSP LTDA. Con esta transferencia tecnológica se busca mejorar mediante una solución dual celular/satelital, versátil, económica, de bajo consumo y ceñida a la normatividad internacional FCC y CE Mark, la oferta de servicios inalámbricos para seguimiento de activos móviles.
Diseño, construcción y evaluación de un dispositivo dual con cobertura celular/satelital mediante transferencia tecnológica
Keywords: Servicios basados en localización; Location-based services; GPRS (Servicio general de paquetes vía radio); General Packet Radio Service; Transporte; Transportation; GPRS technology; Satellite device; Location; Tracking; Mobile assets; Activos móviles; Dispositivo satelital; Localización; Seguimiento; Tecnología GPRS